Diagnostic and prognostic values of tsRNAs in lung cancer: a meta-analysis - Cheng Tang; Su-Xia Sun; Chao Gu; Chao-Juan Li; Jin Xu; Ke-Lei Su; Dan-Dan Zhou; Kuai Yu; Qing-Ling Xiao; Xiao-Li Chen (BMC Cancer)
Abstract Background Lung cancer (LC) is the leading cause of cancer-related death in humans. tRNA-derived small RNA (tsRNA) is a novel biomarker that plays a crucial role in the genesis and development of LC. In this study, we aimed to investigate the value of differentially expressed tsRNAs in LC through meta-analysis. Methods PubMed and Web of Science were searched for articles published up to January 10, 2024. Diagnostic odds ratios (DORs) and areas under the receiver operating characteristic curve (AUCs) were used to evaluate the potential of tsRNAs as diagnostic markers for LC. Furthermore, hazard ratios (HRs) and 95% confidence intervals (95% CIs) were used to analyze association of tsRNAs with LC prognosis. Results In total, 12 studies were included in the analysis. Our results indicated that the combined DOR of total tsRNAs for LC diagnosis was 7.32; the AUC was 0.81. Subgroup analysis revealed that high levels of tsRNAs in serum had good diagnostic efficacy (DOR = 16.56, AUC = 0.88). Moreover, a high tsRNAs level was associated with a worse prognosis in LC patients (HR = 1.59, 95% CI: 1.33–1.90). Conclusion Our findings suggest that a high tsRNAs level has potential value for diagnosis and prognosis of LC patients. However, further high-quality studies are needed to validate our results.